Writings on the Sober Life : The Art and Grace of Living Long - Alvise Cornaro (University of Toronto Press, 2014)
â€œTrattato de la Vita Sobriaâ€ [treatise on the sober life] appeared in November 1558, printed by Grazioso Percacino of Padua. Cornaro followed it up with three other works, which â€“ collected and published by his grandson in 1591 under the general title Discorsi della Vita Sobria [discourses on the sober life] â€“ became a worldwide success. The present work proposes the first complete and corrected edition of Cornaroâ€™s texts, and a review of the history of their birth and their long and fortunate life.**